Pengaruh PENGARUH MODEL BRALANCING BERBASIS TRI PARARTHA TERHADAP SIKAP KEWARGAAN PADA PENDIDIKAN PANCASILA KELAS IV GUGUS VII KECAMATAN SUKASADA - Sudiami, Ketut; Ni Putu Candra Prastya Dewi; I Made Ari Winangun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Fostering character and civic dispositions among elementary school students faces challenges due to learning processes that tend to be monotonous, cognitively oriented, and lacking in the integration of local wisdom. This study aims to analyze the impact of the Tri Parartha-based Bralancing (Brain Balance Learning) model on civic dispositions within the fourth-grade Pancasila Education subject in Cluster VII, Sukasada District. This was demonstrated by the results of an Independent Samples Test using SPSS version 23.0 for Windows, which showed a calculated t-value of -15.536 and a significance value (Sig. 2-tailed) of 0.000 a figure lower than the 0.05 significance level (0.000 < 0.05). Consequently, the null hypothesis (H₀) was rejected, and the alternative hypothesis (H₁) was accepted. The implementation of the *Tri Parartha*-based Bralancing model fosters active, enjoyable, collaborative, and meaningful learning by balancing right- and left-brain activities and integrating the values ​​of *Asih* (compassion), *Punia* (generosity/service), and *Bhakti* (devotion) into the instructional process. These conditions enable students to participate actively, collaborate, express their opinions, and apply civic values ​​in their daily lives. Thus, the *Tri Parartha*-based Bralancing model proved more effective in enhancing students' civic dispositions compared to conventional instruction, based on the civic disposition outcomes observed among fourth-grade students in Cluster VII, Sukasada District, who were taught using the Bralancing model versus those taught using conventional methods.